2018
DOI: 10.1016/s1474-4422(18)30126-1
|View full text |Cite
|
Sign up to set email alerts
|

Potential genetic modifiers of disease risk and age at onset in patients with frontotemporal lobar degeneration and GRN mutations: a genome-wide association study

Abstract: National Institute on Aging, National Institute of Neurological Disorders and Stroke, Canadian Institutes of Health Research, Italian Ministry of Health, UK National Institute for Health Research, National Health and Medical Research Council of Australia, and the French National Research Agency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
84
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 24 publications
5
84
0
Order By: Relevance
“…With respect to sporadic TDP-43 proteinopathies and those caused by GRN mutations, common variants within the TMEM106B gene that increase its expression were found to increase the risk and were associated with shorter disease duration in FTD cases; the major allele (T) increased the risk and was associated with a shorter disease duration, while the minor allele (G) had protective effects 23. In GRN carriers, the presence of the TMEM106B risk allele was also found to reduce the age of onset by approximately 13 years compared with those without it,24 although this association was not confirmed in a recent GWAS study of GRN -related FTD 25. In the latter study, another variant that leads to increased expression of the GFRA2 gene was also found to be associated with increased risk for GRN -related FTD 25.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…With respect to sporadic TDP-43 proteinopathies and those caused by GRN mutations, common variants within the TMEM106B gene that increase its expression were found to increase the risk and were associated with shorter disease duration in FTD cases; the major allele (T) increased the risk and was associated with a shorter disease duration, while the minor allele (G) had protective effects 23. In GRN carriers, the presence of the TMEM106B risk allele was also found to reduce the age of onset by approximately 13 years compared with those without it,24 although this association was not confirmed in a recent GWAS study of GRN -related FTD 25. In the latter study, another variant that leads to increased expression of the GFRA2 gene was also found to be associated with increased risk for GRN -related FTD 25.…”
Section: Introductionmentioning
confidence: 94%
“…In GRN carriers, the presence of the TMEM106B risk allele was also found to reduce the age of onset by approximately 13 years compared with those without it,24 although this association was not confirmed in a recent GWAS study of GRN -related FTD 25. In the latter study, another variant that leads to increased expression of the GFRA2 gene was also found to be associated with increased risk for GRN -related FTD 25. The same major allele of TMEM106B associated with sporadic and GRN -related FTD also conferred an increased risk for C9orf72 -related FTD and FTD-MND, but not MND 26.…”
Section: Introductionmentioning
confidence: 96%
“…A considerable body of literature has historically shown that AD and DLB are characterized by a deficit in short latency afferent inhibition (SAI), a marker of sensorimotor integration that largely relies on cholinergic circuits, and FTD and DLB show a striking alteration in short interval intracortical inhibition and facilitation (SICI‐ICF), which substantially depend on GABAergic and glutamatergic circuits, respectively. These findings have prompted subsequent studies, which have suggested that a neurophysiological assessment might not be far from being ready to be translated from the experimental to the clinical setting . However, to further confirm TMS utility for the diagnosis of AD and other neurodegenerative dementias and to extend its use broadly, multicenter studies assessing the best combination of TMS measures, thus achieving the highest classification performance, are desirable.…”
mentioning
confidence: 99%
“…These findings have prompted subsequent studies, which have suggested that a neurophysiological assessment might not be far from being ready to be translated from the experimental to the clinical setting. [26][27][28][29][30] However, to further confirm TMS utility for the diagnosis of AD and other neurodegenerative dementias and to extend its use broadly, multicenter studies assessing the best combination of TMS measures, thus achieving the highest classification performance, are desirable.…”
mentioning
confidence: 99%
“…In contrast to the SNP-based results, the gene-based analyses using MAGMA elicited a third locus on chromosome 7 (7p21.3) at transmembrane protein 106B (TMEM106B) showing genome-wide significant association with CSF NF-L levels ( Figure 1B, Table 2, and Supplementary Table 1). This gene, which is an established genetic risk modifier for frontotemporal lobar degeneration (FTLD) 27,28 , contains 187 SNPs of which the majority (n = 124 SNPs) are in strong LD (r 2 >0.6) with the lead variant in TMEM106B, i.e., rs1548884 (single SNP P = 2.62E-07, Table 2 and Supplementary Table 1). algorithm.…”
Section: Gwas Analyses Using Csf Neurofilament Light (Nf-l) Levelsmentioning
confidence: 99%